2017
DOI: 10.1089/ten.tea.2016.0405
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Presence Prevents Removal of Antigenic Nuclear-Associated Proteins from Bovine Pericardium for Heart Valve Engineering

Abstract: Current heart valve prostheses are associated with significant complications, including aggressive immune response, limited valve life expectancy, and inability to grow in juvenile patients. Animal derived "tissue" valves undergo glutaraldehyde fixation to mask tissue antigenicity; however, chronic immunological responses and associated calcification still commonly occur. A heart valve formed from an unfixed bovine pericardium (BP) extracellular matrix (ECM) scaffold, in which antigenic burden has been elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…Indeed, this finding is supported by previous work, which demonstrated that removal of hydrophilic antigens only resulted in increased cell-mediated and humoral immune response compared to removal of both hydrophilic and lipophilic antigens[13]. Importantly, the present study demonstrates that ASB-16 at an optimal concentration of 3%, in the absence of magnesium chloride, is essential to overcome both hydrophilic and lipophilic antigen mediated graft-specific humoral responses [20,21,38]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, this finding is supported by previous work, which demonstrated that removal of hydrophilic antigens only resulted in increased cell-mediated and humoral immune response compared to removal of both hydrophilic and lipophilic antigens[13]. Importantly, the present study demonstrates that ASB-16 at an optimal concentration of 3%, in the absence of magnesium chloride, is essential to overcome both hydrophilic and lipophilic antigen mediated graft-specific humoral responses [20,21,38]. …”
Section: Discussionsupporting
confidence: 87%
“…Lipophilic antigen removal plateaued at 79% removed for ASB-14 at 5% w/v and 92% removed for ASB-16 at 3% w/v. Although neither detergent statistically increased hydrophilic antigen removal compared to no detergent use, the level of hydrophilic antigen removal achieved was greater than any previously reported method for both ASB-14 (95%) and ASB-16 (96%) [13,20,38]. The results of this study demonstrate that although sulfobetaines show great promise in solubilization and subsequent removal of lipophilic antigens from bovine pericardium, the ability of individual sulfobetaines to achieve antigen removal cannot be predicted from their solubilizing profile determined through analytical chemistry.…”
Section: Discussionmentioning
confidence: 56%
“…Chelators such as ethylenediaminetetraacetic acid (EDTA) detach these cations from cell membrane binding sites and release cell components out of ECM [48,93]. Furthermore, chelators may facilitate removing nuclear immunogens via depleting free divalent cations, which precipitate DNA on ECM [94]. However, mere EDTA treatment is insufficient to achieve suitable acellular ECM scaffolds [95].…”
Section: Chemical and Biological Agentsmentioning
confidence: 99%
“…Salts containing magnesium, calcium, and other divalent cations may precipitate nuclear antigens and hinder the solubilization and elimination of nuclear antigens from ECM. They also may co-precipitate DNA-related proteins [94].…”
Section: Solubilizationmentioning
confidence: 99%